HOW TO TEACH BILINGUAL PROGRAM? : AN APPLICATION OF CONTENT AND LANGUAGE INTEGRATED LEARNING ON PRIMARY SCHOOL - Nugraha, Trisna; Nurhasanah, Nurhasanah; Fuadah, Ulfah Samrotul; Mutiasih, Palupi (P2M STKIP Siliwangi, 2020)
In the last decade, education systems around the world have prioritized increasing students’ literacy and numeracy skills. The increasing need for language literacy has resulted in the emergence of a trend bilingual program in primary schools. This research was motivated by the learning problems that occurred in the first year bilingual program. The study aims to see the effectiveness of the Content and Language Integrated Learning (CLIL) approach on the competence of sains curriculum content and students' language skills. The research method used was Classroom Action Research (CAR) with the research subject being the first year students of the bilingual program who were stand on grade 4th primary school (n = 21). Data analysis not only focuses on increasing scores in each cycle, but also obtains new findings about the stability between science content abilities (non-language) and second language skills (english). Initial data explains that only 25% of students meet the learning completeness aspect. Along with the end of the third cycle, the study found that 85% of students could complete learning completeness. The study concluded that the CLIL was able to stably improve content and language skills with certain improvement criteria. The findings from the improvement of this cycle can be used as a reference for developing CLIL research in primary schools especially on bilingual programs.